Achieving operational tolerance in transplantation: how can lessons from the clinic inform research directions? - Chandrasekharan, D; Issa, F; Wood, K (2013)
Since the first solid organ transplant between the Herrick twins in 1954, transplantation immunology has sought to move away from harmful immunosuppressive regimens towards tolerogenic strategies that promote long-term graft survival. This has required a concerted multinational effort with scientists and clinicians working towards a common goal. Reports of immunosuppression-free kidney and liver allograft recipients have provided the proof-of-principle, but intentional generation of tolerance in clinical transplantation is still only achieved infrequently. Recently, there have been an increasing number of encouraging developments in the field in both experimental and clinical studies. In this article, we review the latest advances in tolerance research and consider possible future barriers and solutions in achieving reliable graft acceptance in the long term.